(untitled) (Research, Society and Development, 2021)
Objective: to report the experience of an operative group on "motivation for treatment" for people with needs derived from the consumption of alcohol, crack and other drugs. Method: Descriptive study, as a experience report, carried out during the practices of the discipline. Care process in mental health from the University of the International Integration of Lusofonia Afro-Brazilian, during the month of July / 2019. 19 users of a host unit, in the city of Fortaleza-CE, will attend the group activity. The action was executed in three moments: "the approach with the group, theme’s presentation and performance of the subject, and the closure." Results: They prove that this type of action is effective to understand better the obstacles and difficulties that users face, to improve interventions, in addition, face the issue becomes a basic need for them to overcome the substance’s phase withdrawal . Conclusion: the existence of a positive influence of the operative group was confirmed for the members of the unit who reported it to be a fundamental experience for their treatment and for the students it was possible to understand in practice better the dynamics for conducting the groups.